(untitled) (Bangladesh Journal of Neuroscience, 2013)
Objective: To determine the frequency and characteristics of carotid artery stenosis in acute ischemic stroke patients and to assess the significance of common risk factors for carotid stenosis in these patients. Method: It was cross-sectional observational study which was carried out in neurology department of Bangabandhu Sheikh Mujib Medical University (BSMMU) during the period of January 2010 to December 2011 and one hundred patients admitted with acute ischemic stroke were included in the study. Doppler ultrasound was performed during hospitalization to find out carotid artery stenosis. Statistics analysis was done with SPSS - 14. Results: Out of one hundred (100) patients, eighty (80%) were males and twenty were (20%) were females. The patients were dividing into two groups with and without carotid stenosis. Less than 50% carotid artery stenosis (insignificant stenosis) was seen in 40% ( n=40) cases and significant stenosis was seen in 60% (n=60) patients. Overall 86% (n= 46) out of 60 patients were found to have carotid artery stenosis on the ipsilateral side corresponding to the ischemic lesion and 19% (n=11) had stenosis on the contralateral side. Out of significant stenosis ,mild (50% stenosis) in 12% (n=7) patients, moderate ( 51-69% ) stenosis in 50%( n= 30 ) patients and severe (>70%) stenosis in twenty (n=33%) patients . Near total occlusion was seen in three (5%) patients. The presence of stenosis was significantly correlated with older age and the presence of multiple risk factors. Conclusion: Carotid artery stenosis is strongly associated with ischemic stroke. Doppler studies are recommended for the high risk patients for the primary as well as secondary prevention of ischemic stroke. DOI: http://dx.doi.org/10.3329/bjn.v28i2.17172 Bangladesh Journal of Neuroscience 2012; Vol. 28 (2): 67-73